Sleeved concrete cylinders subject to hard impact - Prichard, Sarah J. (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2000)
The purpose of this thesis is to determine the response of sleeved concrete cylinders to low velocity hard impact. Previous research has shown that, when concrete is uni-axially loaded and subject to the high strain rates associated with impact, it consistently exhibits a greater strength and stiffness than when statically loaded. Furthermore, other research has shown that when concrete is confined in two out of three mutually perpendicular directions its compressive strength in the third direction is considerably enhanced
Keywords: Civil Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin